Analisis Efisiensi Konsumsi Daya Listrik di Bank X Surabaya - Affan Bachri; Kemal Farouq Mauladi; Arief Budi Laksono; andi andi Rudianto (KOMPUTEK, 2024)
Such advances in science and technology are growing more rapidly, making electrical energy a very important source of energy for human life. The importance of electrical energy in everyday life and in the development that is being carried out, demands a reliable and efficient electrical system in technical and cost aspects that can serve and meet human needs well. The method carried out uses observation techniques in the field to find out real data in the field, uses comparative techniques to compare two sample variables or two different times, and uses data collection techniques such as electricity bill accounts, single line charts and dena of the Bank X Surabaya building.From the calculation of the cost of electricity account bills at the Bank X Surabaya Building, which is 528,174 kWh / year with an initial IKE value of 396 kWh / Year is said to be wasteful in the use of electrical energy according to the Energy Consumption Intensity (ECI) standard, where the Energy Consumption Intensity (ECI) standard in Office Buildings is 240 kWh / year. So from the analysis carried out, it was found that Energy Saving Opportunities (ESO) in the lighting system obtained the results of reducing electrical energy consumption for one year, which was 37.4% with savings of 9,912 kWh / Year and in the air conditioning system obtained Saving electrical energy by 29% with savings of 8,565 kWh / Year. Electrical Energy Saving Opportunities in Bank X Surabaya Building are obtained by conducting energy audits from existing data sources in the building and calculating all power loads. After a detailed audit, it was found that Energy Saving Opportunities (ESO) were replaced by CFL lamps, TL Fluorescent into LED lamps. And for the air conditioning system by replacing Non-Inverter AC into Inverter AC.